EDUKASI KESEHATAN MAKANAN BEBAS TOKSIK DALAM MENGHADAPI PANDEMI COVID-19 - Mamay; Muhammad Hadi Sulhan; N. Ai Erlinawati (LP4M STIKes Karsa Husada Garut, 2021)
The COVID-19 pandemic outbreak has occurred over the past year throughout the country. In addition to maintaining distance, washing hands and wearing masks, another way to prevent COVID19 is to increase or body immunity. The use of additives in food has a toxic impact. The risk of using food additives in large quantities will pose a big risk to the immune system or the body's immunity against various disorders and diseases so that it is easy to contract COVID-19. Therefore, it is important to consume toxic-free foods that do not reduce immunity so that it is not easy to contract diseases in the face of COVID -19. The method of implementing this community service goes through 3 stages, namely: preparation, implementation and documentation. Implementation of community service through the zoom application to reduce and prevent the transmission of COVID-19. Participants who attended were 68 high school and vocational high school students. Health education for high school and vocational high school students was successfully carried out as an activity to prevent and control COVID-19 by increasing the body's immunity through consuming toxic-free foods that reduce the risk of contracting COVID-19.